(untitled) (Bangladesh Journal of Medical Science, 2026)
Objective is to improve the functional state of women between 30- 40 years of age who suffer from somatoform vegetative dysfunction. Methods The pedagogical experiment was conducted at a fitness club for 8 months. It involved 36 women between 30- 40 years of age who suffer from somatoform vegetative dysfunction and have an average level of functional state. They were engaged in an experimental method of conducting classes using physical exercises with the use of fitness loads of moderate intensity. To assess the functions of the cardiovascular system, blood pressure and pulse were measured using a tonometer. To analyze the state of the cardiovascular system, the endurance coefficient was calculated using the Kvass formula. The tolerance to hypoxia was determined using the Gench and Stange test. The Quetelet index was calculated based on height and weight indicators. Results During the study period, in the experimental group the pulse rate decreased by 6.75 bpm (p<0.05). An increase in systolic pressure was 4.5%, and in diastolic pressure – 2.5% (p>0.05). The endurance coefficient decreased by 2.78 (p>0.05). The improvement of the Gench test was 27.7% (p<0.05), and that of the Stange test – 8.2% (p<0.05). The Quetelet index decreased by 0.08 (p>0.05). Conclusion The level of the functional state of the body of women, who suffer from various somatoform vegetative dysfunction, improves significantly if physical exercises with moderate intensity fitness loads are used in fitness classes according to the developed physical rehabilitation technique. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 925-935